The Macroeconomic Projections of the German Government: A Comparison to an Independent Forecasting Institution - Robert Lehmann; Timo Wolllmershäuser (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper investigates the macroeconomic projections of the German government since the 1970s and compares it those of the Joint Economic Forecast, which is an in-dependent forecasting institution in Germany. Our results indicate that nominal GDP projections are upward biased for longer forecast horizons, which seems to be driven by a false assessment of the decline in Germany's trend growth and a systematic failure to correctly anticipate recessions. We show that the German government also deviates from the projections of the Joint Economic Forecast, which in fact worsened the forecast accuracy. Finally, we find evidence that these deviations are driven by political motives.
Keywords: E30; E37; E39; 330; macroeconomic forecasting; forecast accuracy; independent forecasting; political economic biases